Phenomenology of ultrafine particle concentrations and size distribution across urban Europe. (February 2023) - Trechera, Pedro; Garcia-Marlès, Meritxell; Liu, Xiansheng; Reche, Cristina; Pérez, Noemí; Savadkoohi, Marjan; Beddows, David; Salma, Imre; Vörösmarty, Máté; Casans, Andrea; Casquero-Vera, Juan Andrés; Hueglin, Christoph; et al.
Highlights: The phenomenology of urban ultrafine particles in 16 cities of Europe is presented. N to S&E Europe increasing urban background concentration trends are evidenced. Road traffic emissions is the main source of ultrafine particles in urban Europe. High midday concentrations independent of traffic influence occur in many cities. There is an urgent need to harmonize measurements and making the data open. Abstract: The 2017–2019 hourly particle number size distributions (PNSD) from 26 sites in Europe and 1 in the US were evaluated focusing on 16 urban background (UB) and 6 traffic (TR) sites in the framework of R esearch I nfrastructures services reinforcing air quality monitoring capacities in European URBAN & industrial areaS (RI-URBANS) project. The main objective was to describe the phenomenology of urban ultrafine particles (UFP) in Europe with a significant air quality focus. The varying lower size detection limits made it difficult to compare PN concentrations (PNC), particularly PN10-25, from different cities. PNCs follow a TR > UB > Suburban (SUB) order. PNC and Black Carbon (BC) progressively increase from Northern Europe to Southern Europe and from Western to Eastern Europe. At the UB sites, typical traffic rush hour PNC peaks are evident, many also showing midday-morning PNC peaks anti-correlated with BC. These peaks result from increased PN10-25, suggesting significant PNC contributions from nucleation, fumigation and shipping. Site types to be identified by daily and seasonal PNC and BC patterns are: (i) PNC mainly driven by traffic emissions, with marked correlations with BC on different time scales; (ii) marked midday/morning PNC peaks and a seasonal anti-correlation with PNC/BC; (iii) both traffic peaks and midday peaks without marked seasonal patterns. Groups (ii) and (iii) included cities with high insolation. PNC, especially PN25-800, was positively correlated with BC, NO2, CO and PM for several sites. The variable correlation of PNSD with different urban pollutants demonstrates that these do not reflect the variability of UFP in urban environments. Specific monitoring of PNSD is needed if nanoparticles and their associated health impacts are to be assessed. Implementation of the CEN-ACTRIS recommendations for PNSD measurements would provide comparable measurements, and measurements of <10 nm PNC are needed for full evaluation of the health effects of this size fraction.